Ca2+ signaling in postsynaptic neurons: Neuroplastin-65 regulates the interplay between plasma membrane Ca2+ ATPases and ionotropic glutamate receptors. (September 2022) - Malci, Ayse; Lin, Xiao; Sandoval, Rodrigo; Gundelfinger, Eckart D.; Naumann, Michael; Seidenbecher, Constanze I.; Herrera-Molina, Rodrigo
Highlights: Np65 controls PMCA levels and thereby shapes postsynaptic Ca2+ transients. Np65 controls GluA1-containing AMPA receptor levels in hippocampal neurons. The PMCA-iGluR interplay, critical for postsynaptic Ca2+ signaling, depends on Np65. Np65-PMCA-dependent synaptic plasticity is regulated by GluN2Acontaining NMDA receptors. The PMCA-iGluR interplay appears disturbed in Np-deficient mice with retrograde amnesia. Abstract: Upon postsynaptic glutamate receptor activation, the cytosolic Ca 2+ concentration rises and initiates signaling and plasticity in spines. The plasma membrane Ca 2+ ATPase (PMCA) is a major player to limit the duration of cytosolic Ca 2+ signals. It forms complexes with the glycoprotein neuroplastin (Np) isoforms Np55 and Np65 and functionally interplays with N-methyl-D-aspartate (NMDA)-type ionotropic glutamate receptors (iGluNRs). Moreover, binding of the Np65-specific extracellular domain to Ca 2+ -permeable GluA1-containing α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA)-type ionotropic glutamate receptors (iGluA1Rs) was found to be required for long-term potentiation (LTP). However, the link between PMCA and iGluRs function to regulate cytosolic Ca 2+ signals remained unclear. Here, we report that Np65 coordinates PMCA and iGluRs' functions to modulate the duration and amplitude of cytosolic Ca 2+ transients in dendrites and spines of hippocampal neurons. Using live-cell Ca 2+ imaging, acute pharmacological treatments, and GCaMP5G-expressing hippocampal neurons, we discovered that endogenous or Np65-promoted PMCA activity contributes to the restoration of basal Ca 2+ levels and that this effect is dependent on iGluR activation. Super-resolution STED and confocal microscopy revealed that electrical stimulation increases the abundance of synaptic neuroplastin-PMCA complexes depending on iGluR activation and that low-rate overexpression of Np65 doubled PMCA levels and decreased cell surface levels of GluN2A and GluA1 in dendrites and Shank2-positive glutamatergic synapses. In neuroplastin-deficient hippocampi, we observed reduced PMCA and unchanged GluN2B levels, while GluN2A and GluA1 levels were imbalanced. Our electrophysiological data from hippocampal slices argues for an essential interplay of PMCA with GluN2A- but not with GluN2B-containing receptors upon induction of synaptic plasticity. Accordingly, we conclude that Np65 may interconnect PMCA with core players of glutamatergic neurotransmission to fine-tune the Ca 2+ signal regulation in basal synaptic function and plasticity. Graphical abstract: Image, graphical abstract